Modulation of reactivity of singlet radical pair in continuous flow: photo-fries rearrangement - Karjule, Neeta; Sharma, Mrityunjay K.; Nithyanandhan, Jayaraj; Kulkarni, Amol (Journal of Photochemistry and Photobiology A: Chemistry, 2018)
Photo-Fries rearrangement of phenyl benzoate is studied using continuous flow for modulating the reactivity of singlet radical pair by changing the viscosity of the solvent. The effect of flow and proximity of the reactants with the light source on the reactivity of radical pair, formed from singlet excited state was investigated in details. In non-viscous solvent, the results from flow synthesis were comparable to batch reactor. In viscous solvents, selectivity of ortho- and para-isomers (o-/p- isomer) of the product could be controlled by changing viscosity as well as the flow rate. Using flow synthesis, ortho- and para-isomer ratio was obtained as high as 8.45 which are twice as compared to batch experiment with in fraction of residence time.